The use of lipid-lowering therapy and effects of antihyperglycaemic therapy on lipids in subjects with type 2 diabetes with or without cardiovascular disease: a pooled analysis of data from eleven randomized trials with insulin glargine 100 U/mL - Markolf Hanefeld; Louise Traylor; Ling Gao; Wolfgang Landgraf (Cardiovascular Diabetology, 2017)
Abstract Background Dyslipidaemia is a major contributor to the increased risk of cardiovascular disease (CVD) associated with type 2 diabetes (T2D). This study aimed to characterize the extent of lipid-lowering therapy use and its impact on lipid and glycaemic outcomes in people with T2D uncontrolled on oral agents who were enrolled in insulin glargine 100 units/mL (Gla-100) randomized controlled trials (RCTs). Methods A post hoc patient-level pooled analysis of eleven RCTs (≥24 weeks’ duration) comparing Gla-100 (±oral antidiabetes drugs [OADs]) with OADs alone in people with T2D was performed. Baseline and Week 24 or study endpoint lipid status (low-density lipoprotein cholesterol [LDL-C], high-density lipoprotein cholesterol [HDL-C], non-high-density lipoprotein cholesterol [non-HDL-C] and triglycerides) and indices of glycaemic control (glycosylated haemoglobin, fasting plasma glucose [FPG]) were examined in patient groups according to treatment received and CVD status. Lipid-lowering therapy was provided at the discretion of physicians at baseline and throughout the studies. Results Of the 4768 participants included in the analysis, 41% (n = 1940) received lipid-lowering therapy. Only 51% of participants with CVD (1885/3672) were treated with lipid-lowering therapy; these participants had significantly lower levels of LDL-C, HDL-C and non-HDL-C, and higher levels of triglycerides versus patients not treated with lipid-lowering therapy at baseline and study endpoint (P < 0.001 for all). Antihyperglycaemia therapy resulted in decreases in glycosylated haemoglobin (−1.4 to −1.6%) and FPG (−68.9 to −75.3 mg/dL) at Week 24. Furthermore, slight improvements in non-HDL-C (−3.9 to −9.1 mg/dL) and triglyceride levels (−25.8 to −51.2 mg/dL) were observed. Similar changes were seen irrespective of lipid-lowering therapy or CVD status. Conclusions In a T2D cohort included in Gla-100 clinical studies, many participants with T2D and CVD did not receive lipid-lowering therapy, and for most categories of lipid the levels were outside the optimal range. Even in patients treated with antihyperglycaemic therapy but not lipid-lowering therapy, there were modest improvements in non-HDL-C and triglyceride levels in all participants with T2D and CVD. There is a need for increased implementation of guideline recommendations such as American College of Cardiology/American Heart Association for the management of dyslipidaemia in patients with T2D.